The Role of the Seminar “From Education to Action: A Guided Community, Waste-Free Pekanbaru” in Increasing Public Awareness and Participation in Waste Management in Sungaisibam, Pekanbaru City - Ahmad Jamaan; Arruhul Jadid; Intan Purwati; Najwa Amelia; Chaironi C; Hikmah Syahrinni; Havivah H; Salsabila S; Dhaffa Raychan Sihombing; Chalisha Haura Putri Suharmanto; Tasya Nadia Putri; Zihni Karim Azizi (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Urban waste management in Pekanbaru, including Sungaisibam village, remains a significant and complex challenge requiring a comprehensive solution. Low public awareness and participation are often the main factors hindering the effectiveness of waste management programs. This community service research aims to analyze the role of an educational seminar in increasing public awareness and participation in 3R-based (Reduce, Reuse, Recycle) waste management. This study uses a qualitative approach with a case study method to analyze the event's implementation, its relevance to local policy, and its impact on participants. The results indicate that the seminar functioned as an effective catalyst, successfully bridging the gap between knowledge and action. This success was underpinned by three key factors: first, its alignment with the Pekanbaru City Government's policy of transitioning to a Waste Management Agency (LPS)-based system; second, strong social support from the presence of government officials and expert speakers; and third, an interactive and action-oriented event design that aligns with the principles of the Theory of Planned Behavior. The seminar not only provided information but also built motivation, created a social norm, and enhanced the community's awareness of their ability to participate actively.